(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Panchayat Raj Institutions are regarded as the remedy for all rural development challenges and are associated with the empowerment of marginalized groups, particularly women. This study offers an overview by topic of the empowerment of women representatives in Panchayati Raj Institutions within the framework of the decentralization process and the 73rd Constitutional Amendment in India, addressing Panchayat operations, self-determination capabilities, engagement in community activities, awareness of socio-economic changes, decision-making authority at the Panchayat level, and political participation. The participation of female MPs, notably those from marginalized groups, has significantly expanded in recent years mostly due to affirmative action. Numerous studies suggest that female leaders exhibit lower levels of corruption, deliver higher-quality public products at competitive costs, and prioritize women’s concerns to enhance overall governance. Conversely, research has indicated that female representatives are often illiterate and reliant on their spouses and male authorities for decision-making, particularly in relation to rural development initiatives. The review indicates that women’s political advancement is challenging in a patriarchal and caste-dominated society, resulting in numerous difficulties for female members of the Gram Panchayat. Female representatives experience discomfort in functioning at the Panchayat level due to the predominance of male representatives, and they require more time to demonstrate their competence compared to their male counterparts. Additionally, it was discovered that male representatives allocate more time to political activity, whilst females dedicate more time to domestic responsibilities. The 73rd Amendment’s affirmative action has empowered women and underprivileged communities, however they have not yet achieved parity. Numerous scholars have noted that Scheduled Castes, Scheduled Tribes, and women are poised to advance in their social status, leadership positions, economic standing, educational attainment, and political consciousness and accomplishments during the coming decade.